Strategic Line Balancing for Enhanced Efficiency in Solar Module Manufacturing: A Comprehensive Study in the Renewable Energy Sector - Imansuri, Febriza; Sumasto, Fredy; Pratama, Indra Rizki; Aminuddin, Muhammad; Saputra, Alfiolani (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
This study endeavors to enhance the productivity of solar module production in a renewable energy conversion company. The existing production line needs help in achieving the daily target of 64 units, resulting in an actual output of only 40 units. This study focuses on optimizing the production line by considering processing time adjustments and operator flexibility. To accurately measure working time, we incorporate operator flexibility and adjustment factors in the planning phase of solar module production. The primary objective is establishing an optimal production trajectory by balancing the load and capacity across workstations, thereby elevating overall production efficiency. The approach involves the application of the trial-error method and the shortest operation time method, implemented through POM QM software. Through meticulous data analysis, we determine that the trial-error process yields the most optimal results. Post-implementation, improvements are evident as the solar module production capacity increases to 60 units per day from the initial 40 units. Additionally, the idle time ratio on the assembly line to available time diminishes to 13.17% after optimization. This study contributes valuable insights into the effective enhancement of solar module production lines, emphasizing practical methodologies and software-assisted techniques for achieving substantial productivity gains in the renewable energy sector.